Eve - LaValle, Victor, 1972- (BOOM! Studios, 2022)
A young girl, Eve, raised in a virtual reality, embarks on a deadly cross-country quest to save her father... and the dying planet. She's accompanied by Wexler, her robotic caretaker and protector, sheathed in her favorite teddy bear.